The Economic and Technical Feasibility of the Application of Partial Nitritation Anammox Technology Over Conventional Nitrification Denitrification for the Treatment of Sidestream Liquor at Cape Flats WWTP - Jelliman, Shanen (Department of Civil Engineering, 2022)
The objective of this study was to provide a comparative analysis for treating sidestream liquor from a future regional anaerobic digestion (AD) facility (Thermal Hydrolysis Process (THP)+AD) at Cape Flats WWTP in South Africa. The study focused on comparing a conventional nitrification denitrification (Modified Ludzack-Ettinger (MLE) configuration) with a novel partial nitritation/ anammox (PN/A) process. The sidestream liquor was characterised by mass balance over the AD process. Steady-state models were used to predict equipment sizes and determine the process efficiency for each treatment technology. The models were evaluated using an effluent quality index (EQI) and operational cost index (OCI). The capital cost of each treatment solution was calculated and used to perform an economic lifecycle cost analysis (LCCA). The study concluded that the sidestream liquor (untreated) would recycle 3 415 kg TKN/d back to the mainstream process which represented 29% of the design capacity of the plant. The MLE process required a 53% smaller reactor volume but consumed 93% more energy and produced 64% more sludge which resulted in the MLE OCI being 10.2 times higher than the PN/A process. The total capital cost of the PN/A and MLE processes were calculated to be R139 537 000 and R117 420 000 respectively. Although the MLE process costs 16% less to implement initially, the LCCA over a 20-year operational period indicated that the net present value of the MLE process is 2.8 times higher than the PN/A process.